Komunikasi Lingkungan Komunitas Bank Sampah Wijaya Kusuma Dalam Meningkatkan Semangat Peduli Lingkungan (Verba Vitae Unwira, 2020)
This study aims to find out how the environmental communication process carried out by the Wijaya Kusuma Garbage Bank in Griya Persada Elok RW 16 Mustika Jaya Housing, and improve environmental care in the RW 16. This study uses a qualitative approach with a descriptive concept and four communication concepts i.e. environment, assessment, planning, production, action and reflection. Data collection techniques consist of observation, in-depth interviews, and documentation. The data obtained by the author are presented and analyzed using data triangulation. The results of this study indicate that the role of environmental communication towards RW 16 communities helps the community to maintain a clean and comfortable environment in the region itself. With the communication provided by the chairman and management, the community of RW 16 can understand about maintaining a clean and comfortable environment in the area of ??the Wijaya Kusuma RW 16 Waste Bank.
Keywords: Environmental Communication; Environment; Trash; Environmental Communication Concepts; Descriptive Study